Dual-Output CMOS Voltage Squarer Circuit - Boonchu, Boonchai; Surakampontorn, Wanlop (My University, 2020)
A dual-output CMOS voltage squarer circuit has been proposed. The proposed circuit structure is based on the current squarer circuit core. The differential output OTA which is the combination of class-AB amplifier and is employed as current-to-voltage units in order to provide the squarer output in voltage form. The performances of the proposed squarer have been confirmed by circuit simulation employing 0.25 μm CMOS technology. Simulation results show that the circuit performs the squaring function under ±1.5 V power supply voltage and the static power consumption is less than 1.2 mW.
Keywords: class-AB; CMOS squarer; differential output OTA; dual-output; fully differential circuit; squaring circuit